2013
DOI: 10.1155/2013/963520
|View full text |Cite
|
Sign up to set email alerts
|

ROS and Brain Diseases: The Good, the Bad, and the Ugly

Abstract: The brain is a major metabolizer of oxygen and yet has relatively feeble protective antioxidant mechanisms. This paper reviews the Janus-faced properties of reactive oxygen species. It will describe the positive aspects of moderately induced ROS but it will also outline recent research findings concerning the impact of oxidative and nitrooxidative stress on neuronal structure and function in neuropsychiatric diseases, including major depression. A common denominator of all neuropsychiatric diseases including s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
240
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 346 publications
(242 citation statements)
references
References 173 publications
(167 reference statements)
1
240
0
1
Order By: Relevance
“…Previous reports have demonstrated that, under normal conditions, supplementation of CoQ10 [36, 37] or other antioxidant agents does not improve memory performance [9]. Elevated levels of reactive oxygen species are involved in numerous diseases, and they play a key role in several normal physiological processes and signaling pathways of cognitive processes [38-41]. Thus, increasing antioxidant levels and activities in physiological conditions have no beneficial effects on cognition and may even contribute to a decline in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have demonstrated that, under normal conditions, supplementation of CoQ10 [36, 37] or other antioxidant agents does not improve memory performance [9]. Elevated levels of reactive oxygen species are involved in numerous diseases, and they play a key role in several normal physiological processes and signaling pathways of cognitive processes [38-41]. Thus, increasing antioxidant levels and activities in physiological conditions have no beneficial effects on cognition and may even contribute to a decline in this process.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the level of reactive oxygen species (oxygen ions, free radicals and peroxides) leads to oxidative stress, which would alter the neuronal signals that produce neuro-inlammation with neuro-degeneration and implicitly with cognitive impairment [67].…”
Section: Copd: Fundamental Pathophysiological Mechanisms Susceptible mentioning
confidence: 99%
“…In brain tissue, ROS are mostly generated by microglia and astrocytes, and they modulate synaptic and nonsynaptic communication between neurons and glia. 29 Many NPs, including ZnO NPs, can trigger damage to mitochondria and increase the mitochondrial membrane potential. [30][31][32] In the present study, a ROS assay was used to evaluate the change of the ROS level in BV-2 cells after exposure to 50 nm ZnO NPs.…”
mentioning
confidence: 99%